SEJARAH DAN PERKEMBANGAN LEMBAGA PENDIDIKAN MUHAMMADIYAH DI KABUPATEN SUMBAWA NUSA TENGGARA BARAT TAHUN 1940-2014 - Utama, Abdul Alimun (Universitas Muhammadiyah Surakarta, 2017)
Muhammadiyah organization in Sumbawa regency was established on 6 May 1940. The movement and the development of educational institutions Muhammadiyah Sumbawa has been felt by the community. The development of educational institutions Muhammadiyah Sumbawa able to set up education through three lines of education, namely: formal education, non-formal and informal. formal education has been established since the year 1941-2013, thenumber of 23 educational institutions, including; 4 (four) kindergarten Ortom(Autonomous organizations)Aisyiah, 6 (six) elementary and MI (madrasah ibtidaiyah) , 6 (six) SMP (junior high school)and MTS (madrasah tsanawiyah), 6 (six) SMA (Senior High School) and MA (madrasah aliyah), 1 (one) colleges. While informal pathways, include; orphanage, cottage tahfizulquran and manage mosques. As developed through informal education through a variety of program areas stewardship activities Muhammadiyah Sumbawa.Based on the above background, the formulation of the problem in this research is How the History and Development of Institutions of Muhammadiyah in Sumbawa and what are the factors supporting and inhibiting the development of Muhammadiyah Education Institute in Sumbawa. While the purpose of this study was to describe the history and development of educational institutions Muhammadiyah in Sumbawa as well as factors supporting and inhibiting. Based on the research results, indicate that during the struggle for the developmentof educational institutions Muhammadiyahof the year 1952-2014, Muhammadiyah Sumbawa able to give an important role in developingthe educational institutions of Muhammadiyah Sumbawaby providing of islamic guidance,which is realized by three educational paths, is education formal, non-formal and informal. As for enabling and inhibiting factors that influencesuccess of the organization Muhammadiyah Sumbawa in developing educationalinstitutions Muhammadiyah can be seen from several internal and external factors are schools, human resources and educational tools. While the factors that most basic is a factor that is an asset fund the passage of a education, While the inhibiting factors that most basic is a factor that is an asset fund the passage of a education, and unmatched strictly by the state education agency Berdirinya organisasi Muhammadiyah di Kabupaten Sumbawa pada tanggal 6 Mei 1940. Gerakan dan perkembangan lembaga penddikan Muhammadiyah Sumbawa telah dapat dirasakan oleh masyarakat. Perkembangan lembaga penddikan Muhammadiyah Sumbawa mampu mendirikan pendidikan melalui 3 jalur pendidikan, yaitu: pendidikan formal, nonformal dan informal. melalui jalur pendidikan formal telah didirikan dari semnjak tahun 1941-2013, dengan jumlah 23 lembaga pendidikan, meliputi; 4 (empat) jenjang TK Ortom Aisyiah, 6 (enam) jenjang SD dan MI, 6 (enam) jenjang SMP dan MTS, 6 (enam) jenjang SMA dan MA, 1 (satu) jenjang perguruan tinggi. Melalui jalur nonformal, meliputi; panti asuhan, pondok tahfizul qur’an dan mengelola masjid. Adapun melalui pendidikan informal yaitu dikembangkan melaui berbagai program kegiatan bidang-bidang kepengurusan Muhammadiyah Sumbawa. Berdasarkan latar belakang di atas, maka rumusan masalah dalam penelitian ini adalah Bagaimanakah Sejarah dan Perkembangan Lembaga Pendidikan Muhammadiyah di Kabupaten Sumbawa dan apa saja yang menjadi faktor pendukung dan penghambat perkembangan Lembaga Pendidikan Muhammadiyah di Kabupaten Sumbawa. Sedangkan tujuan penelitian ini adalah untuk mendeskripsikan sejarah dan perkembangan lembaga pendidikan Muhammadiyah di Kabupaten Sumbawa serta faktor pendudukung dan penghambatnya. Berdasarkan hasil penelitian, menunjukkan bahwa sepanjang masa perjuangan pengembangan lembaga pendidikan Muhammadiyah dari tahun 1952-2014, Muhammadiyah Sumbawa mampu memberi peranan penting dalam mengembangan lembaga pendidikan Muhammadiyah Sumbawa dengan memberi pedoman keislaman, yang mana diwujudkan melalui tiga jalur pendidikan, yaitu pendidikan formal, nonformal dan informal. Adapun faktor pendukung dan penghambat yang sangat mempengaruhi keberhasilan organisasi Muhammadiyah Sumbawa dalam mengembangkan lembaga pendidikan Muhammadiyah dapat dilihat dari beberapa faktor internal dan eksternal adalah sekolah, SDM, dan alat pendidikan. Sedangkan faktor penghambat yang paling pokok adalah faktor dana yang merupakan aset berjalannya suatu pendidikan, dan tersaingi ketat oleh lembaga pendidikan negeri.